Eat what elephants eat : vegan recipes for a strong body and a gentle spirit - Thompson, Dominick; Gambacorta, Theresa (Simon Element, 2025)
At the heart of Eat What Elephants Eat are eighty simple vegan recipes and meal plans for a vegan lifestyle that anyone can follow. Dom answers questions all vegan-curious people ask: How do I stay focused? What are the health benefits? Is it expensive? (No!) What about protein? (Yes! Lots!)